Supervision of Madrasah Heads and Teacher Performance of Madrasah Tsanawiyah Negeri 1 Serang Regency - Suryapermana, Nana; Paiman, Paiman; Fauzi, Anis; Azizatunnisa, Mila (Journal of Asian Islamic Educational Management (JAIEM), 2025)
The main problem in this study is whether there is a significant relationship between the implementation of supervision of madrasah heads and the improvement of teacher performance. This study aims to find out how much the relationship between the implementation of supervision by madrasah heads in improving teacher performance. This study uses a quantitative descriptive method with data collection instruments in the form of questionnaires, which are collaborated with observations, and documentation to the research location. The population and sample in this study were 50 respondents from MTsN 1 teachers in Serang Regency. In analyzing the research data, descriptive and inferential statistics were used, the normality of the research data was tested and the statistical analysis of variable correlation was carried out using rxy product moment Pearson. The results of this study show that there is a fairly good relationship between the implementation of supervision of madrasah heads and the improvement of teacher performance, the correlation is categorized as sufficient with a value of rxy = 0.56. The contribution of the Madrasah head supervision in improving teacher performance by 31.36%, the rest is influenced by other factors that can be further researched by anyone.